Defesa de direitos humanos e políticas públicas: o tráfico internacional de pessoas no Brasil - Sanchez, Alessandra (2005)
The main concern in this work is to stablish a link between policies and Brazil’s human rights effectiveness. The initial hypothesis is that human rights function standards to accomplish social justice and therefore, should orient public managers. Besides, the ackwnoledgent of civil, political, social and econmical rights are fundamental stones to the conception of the state, of the democracy and liberal political theory. So, promoting human rights through policies is a mesasure of the government’s legitimacy. Simultaneously, human rights play institutional role to the internacional community and also set standards to national states interaction. Nevertheless, human rights can be disrespected by states, private agents and individuals.This work identifies various systnems that enforce human rights. Nowadays inequalities are made worse by globalization and the lack of international courts and institutions that enforce human rights. Globalization can impact people’s lives through mobility. International institutions and NGOs are concerned by the disrespect of human rights superimposed to easy access to mobility. This paper brings the example of trafficking in person for sexuall exploitation to enlighten the fact that this kind of exploitation can only be minimized through effective public policies that aim to reaffirm basic civil rights. The federal government project to face this trafficking situation must be formulated carefully to really enforce the rights it tries to protect. These civil rights should be directly enforced by information campaigns, public security measures and international cooperation agreements. And yet, there is a part of these efforts that should be directed to strengthen social policies that enforce social, economical and cultural rights, but also are likely to diminish people’s vulnerable position. In these kind of policies also lies protection of civil rights.